Risks of SARS-CoV-2 Infection and Immune Response to COVID-19 Vaccines in Patients With Inflammatory Bowel Disease: Current Evidence - Esposito, Susanna; Caminiti, Caterina; Giordano, Rosanna; Argentiero, Alberto; Ramundo, Greta; Principi, Nicola (Frontiers in immunology, 2022)
Inflammatory bowel diseases (IBD), including Crohn’s disease, ulcerative colitis, and unclassified inflammatory bowel disease, are a group of chronic, immune mediated conditions that are presumed to occur in genetically susceptible individuals because of a dysregulated intestinal immune response to environmental factors. IBD patients can be considered subjects with an aberrant immune response that makes them at increased risk of infections, particularly those due to opportunistic pathogens. In many cases this risk is significantly increased by the therapy they receive. Aim of this narrative review is to describe the impact of SARS-CoV-2 infection and the immunogenicity of COVID-19 vaccines in patients with IBD. Available data indicate that patients with IBD do not have an increased susceptibility to infection with SARS-CoV-2 and that, if infected, in the majority of the cases they must not modify the therapy in place because this does not negatively affect the COVID-19 course. Only corticosteroids should be reduced or suspended due to the risk of causing severe forms. Furthermore, COVID-19 seems to modify the course of IBD mainly due to the impact on intestinal disease of the psychological factors deriving from the measures implemented to deal with the pandemic. The data relating to the immune response induced by SARS-CoV-2 or by COVID-19 vaccines can be considered much less definitive. It seems certain that the immune response to disease and vaccines is not substantially different from that seen in healthy subjects, with the exception of patients treated with anti-tumor necrosis factor alone or in combination with other immunosuppressants who showed a reduced immune response. How much, however, this problem reduces induced protection is not known. Moreover, the impact of SARS-CoV-2 variants on IBD course and immune response to SARS-CoV-2 infection and COVID-19 vaccines has not been studied and deserves attention. Further studies capable of facing and solving unanswered questions are needed in order to adequately protect IBD patients from the risks associated with SARS-CoV-2 infection.